Resiliensi Nelayan Kelurahan Malabero Pasca Covid-19 Melalui Pendampingan Pengolahan Hasil Perikanan - Afrima Widanti; Trisna Murni; Willy Abdillah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
This community service aims to increase the resilience of fishermen in the Malabero Urban Village. The method of service is accompaniment. The object of community service is the fishermen’s community in Malabero Village, Bengkulu City. The Covid-19 pandemic has had an impact on fishermen in the Malabero Village. The increase in the unemployed in Bengkulu has reduced people’s purchasing power. Therefore, fishermen need to know how to survive even though the Covud-19 pandemic is not over. Improving fish quality by changing processing methods is one of the best ways to survive. However, the community still needs more information and knowledge. Thus, it is necessary to assist, so that fish processing provides added value. The result of this activity is that the fishing community in Malabero Village is willing to manage fish using a better method.